Examining the Effects of Competency, Discipline, and Organizational Culture on Work Motivation and Its Influence on Employee Performance at Public Services Institution - Seta, Anggada Bayu; Mulyani, Sri; Pratama, Guruh Dwi; Wahyudi, Yuli (Majalah Ilmiah Bijak, 2025)
This study aims to determine the effect of competence, discipline and organizational culture on work motivation which has an impact on employee performance at the Special Correctional Institution (LPKA) Class IIA in Bandung. The method used is explanatory research with a sample of 100 respondents. The analysis technique uses statistical analysis with regression testing, coefficient of determination and hypothesis testing. The results of this study Competence has a significant effect on work motivation of 27.0%, the hypothesis test obtained a significance of 0.000 <0.05. Discipline has a significant effect on work motivation of 46.2, the hypothesis test obtained a significance of 0.000 <0.05. Organizational culture has a significant effect on work motivation of 24.8, the hypothesis test obtained a significance of 0.000 <0.05. Competence, discipline and organizational culture simultaneously have a significant effect on work motivation by 57.8%, the hypothesis test obtained a significance of 0.000 < 0.05. Work motivation has a significant effect on employee performance by 33.0%, the hypothesis test obtained a significance of 0.000 < 0.05.